The Identity of Turritopsis nutricula McCrady 1857 (Hydrozoa, Cnidaria) - Miglietta, Maria Pia; Brandwood, Travis; Mammone, Marta; Martino, Giulio; Giraldo-Meneses, Juliana (Zootaxa, 2026)
Turritopsis nutricula McCrady, 1857, the type species of the genus Turritopsis, has been historically misidentified. This study presents the first comprehensive analysis of medusae morphologically consistent with T. nutricula, and collected from Baldhead Island, North Carolina, in the vicinity of the species’ type locality. Using DNA sequencing of the mitochondrial 16S gene, we provide definitive molecular evidence that distinguishes T. nutricula as a separate lineage within the Turritopsis clade. Our phylogenetic analyses reveal that this species is geographically restricted to the western Atlantic, contradicting earlier claims of its cosmopolitan distribution. Furthermore, we investigate the species’ ability to revert from medusa to polyp, a trait observed in T. dohrnii. Our findings indicate that T. nutricula does not possess this capability, suggesting distinct life cycle characteristics. This research not only clarifies the taxonomic status of T. nutricula but also sets the stage for future genomic studies aimed at understanding reverse development within the genus and the Hydrozoa.